African walnut (Plukenetia conophora) oil promotes glucose uptake while improving energy metabolism and steroidogenesis and maintaining surface architecture in rat testes - Erukainure, Ochuko L.; Chukwuma, Chika I. (Frontiers in Nutrition, 2024)
Background: African walnut (Plukenetia conophora) oil (AWO) has been reported for their nutritional and medicinal properties and has been employed for the management of metabolic diseases including hyperglycemia-mediated ailments.Objective: In the present study, AWO was investigated for its ability to stimulate glucose uptake and its effect on energy metabolism, steroidogenesis and tissue morphology in isolated testes of Sprague-Dawley rats.Methods: Isolated testes. Isolated testes were incubated with AWO (30-240 μg/mL) in the presence of 11.1 mMol glucose at 37 ˚C for 2 h. Control consisted of testes incubated with glucose only, while normal control consisted of testes not incubated with AWO and/or glucose. The standard antidiabetic drug was metformin.Incubation with AWO led to significant increase in glucose uptake, hexokinase, glyoxalase 1, glutathione reductase, glutathione peroxidase, 3β-hydroxysteroid dehydrogenase, 17β-hydroxysteroid dehydrogenase activities, GLUT4, glutathione and ATP levels, while concomitantly suppressing glucose 6-phosphatase, fructose-1,6-biphosphatase, glycogen phosphorylase, aldose reductase, polyol dehydrogenase, ENTPDase, and ATPase activities. Furthermore, incubation with AWO led to improved testicular morphology, while elevating testicular levels of magnesium, sulfur, potassium, calcium and iron. Fatty acid profiling with GC-MS revealed linoleic acid and linolenic acid as the predominant essential fatty acids in AWO. Molecular docking analysis revealed potent molecular interactions of linoleic acid and linolenic acid with GLUT4. These results suggest the ability of African walnut oil to improve testicular glucose metabolism and steroidogenesis and can be explored in the management of male infertility.